2018
DOI: 10.26553/jikm.v9i3.313
|View full text |Cite
|
Sign up to set email alerts
|

Status Gizi Dan Aktivitas Fisik Dengan Status Hidrasi Pada Remaja Di Sma Negeri 5 Kota Jambi

Abstract: Latar Belakang: Hidrasi adalah kondisi dimana orang sehat yang menjaga keseimbangan air. Sekitar 46,1% remaja di indonesia mengalami dehidrasi ringan. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dan aktivitas fisik dengan status hidrasi di SMA Negeri 5 Kota Jambi.                        Metode: Jenis penelitian ini adalah kuantitatif dengan desain studi cross sectional. Sampel penelitian ini berjumlah 90 responden. Analisis data dalam penelitian ini terdiri dari univariat dan bivariat (spear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
1
1
2
Order By: Relevance
“…No significant association can be caused because athletes who have normal or abnormal nutritional status (fat and thin) can still be dehydrated. This study is not in line with the research of Merita et al, (2018) which shows there is a significant relationship between nutritional status and hydration status, namely with p-Value = 0.026 (p<0.05), r = 0.235, and is not in line with the results of other studies that state there is a significant relationship between hydration and obesity. However, this study is in line with research, namely the relationship between nutritional status and hydration status showed meaningless results p = 0.606 (p>0.05).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…No significant association can be caused because athletes who have normal or abnormal nutritional status (fat and thin) can still be dehydrated. This study is not in line with the research of Merita et al, (2018) which shows there is a significant relationship between nutritional status and hydration status, namely with p-Value = 0.026 (p<0.05), r = 0.235, and is not in line with the results of other studies that state there is a significant relationship between hydration and obesity. However, this study is in line with research, namely the relationship between nutritional status and hydration status showed meaningless results p = 0.606 (p>0.05).…”
Section: Resultscontrasting
confidence: 99%
“…Based on the results of research by Merita et al, (2018) related to physical activity factors, the results show that there is a relationship between physical activity and hydration status. Physical activity is also widely known to directly correlate to dehydration status in a dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Gizi pada remaja awal perlu diperhatikan, terutama masalah kekurangan gizi yang berdampak pada gangguan pada reproduksi (4). Sementara itu, remaja yang kelebihan berat badan atau obesitas akan lebih berisiko terkena penyakit degeneratif, seperti hipertensi, diabetes, penyakit jantung koroner, dan lain-lain (5). Penyakitpenyakit inilah yang menjadi penyebab utama dalam kematian di dunia.…”
Section: Pendahuluanunclassified
“…Menurut Pertiwi (2015), sebanyak 45,3% remaja kelas 1 dan 2 di Jakarta mengalami dehidrasi. Penelitian lain yang dilakukan di Jambi juga menunjukkan prevalensi dehidrasi yang hampir sama pada remaja SMA, yaitu sebanyak 42% (Merita, Aisah and Aulia, 2018). Dehidrasi dapat berdampak negatif pada daya tahan fisik seperti melemahnya anggota gerak, hipotonia, hipotensi dan takardia, kesulitan berbicara, bahkan sampai pingsan.…”
Section: Pendahuluanunclassified